Dark matter search with CRESST cryogenic detectors - Angloher, G; Altmann, M; Bruckmayer, M; Bucci, C; Cooper, S; Cozzini, C; Di Stefano, P; von Feilitzsch, F; Frank, T; Hauff, D; Jagemann, T; Jochum, J; et al. (2003)
Results of the CRESST experiment at Gran Sasso using 262-g sapphire calorimeters with tungsten phase transition thermometers are presented. Calibration and analysis methods are described. Data taken in 2000 have been used to place limits on WIMP dark matter particles in the Galactic halo. The sapphire defectors are especially sensitive to low-mass WIMPs with spin-dependent interaction and improve on existing limits in this region. (C) 2003 MAIK "Nauka/Interperiodica".